2020
DOI: 10.1002/cti2.1218
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of COVID‐19 patients with the anti‐CD6 antibody itolizumab

Abstract: Objectives COVID‐19 can lead to a hyperinflammatory state. CD6 is a glycoprotein expressed on mature T lymphocytes which is a crucial regulator of the T‐cell activation. Itolizumab is a humanised antibody targeting CD6. Nonclinical and clinical data in autoimmune diseases indicate that it lowers multiple cytokines primarily involving the Th1/Th17 pathway. The primary objective of this study was to assess the impact of itolizumab in arresting the lung function deterioration of COVID‐19 patients. Secondary objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Canakinumab was evaluated in one retrospective non-controlled study and one case report, 62 63 tesidolumab was assessed in one retrospective study 64 and itolizumab was assessed in a prospective non-controlled study. 65 These studies showed favourable, although very preliminary results, that required to be confirmed in controlled studies.…”
Section: Resultsmentioning
confidence: 95%
“…Canakinumab was evaluated in one retrospective non-controlled study and one case report, 62 63 tesidolumab was assessed in one retrospective study 64 and itolizumab was assessed in a prospective non-controlled study. 65 These studies showed favourable, although very preliminary results, that required to be confirmed in controlled studies.…”
Section: Resultsmentioning
confidence: 95%
“…In general, therapeutic alternatives for patients include the combination of antiviral, anticoagulant and anti-inflammatory drugs [ 51 , 52 ]. Among the latter, in addition to steroids, some immunomodulatory drugs such as tocilizumab, baricitinib and itolizumab, commonly used to treat autoimmune disorders, have been employed in COVID-19 patients [ 53–56 ]. These anti-inflammatory drugs are prescribed in combination with steroids to reduce the so-called cytokine release syndrome or cytokine storm that characterize the hyperinflammatory stage of COVID-19 [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cuban regulatory agency has approved for the trial to use of itolizumab for COVID-19. Itolizumab might interrupt the hyperinflammatory cascade and stop COVID-19 morbidity and mortality [260] .…”
Section: Fluvoxaminementioning
confidence: 99%